FINITE ELEMENT ANALYSIS OF THROUGH THICKNESS EFFECTS ON 300M STEEL STRESS INTENSITY FACTOR - XU Liang; ZHANG Ning; ZHOU Song; WANG Lei; MA Chuang; LIU Peng (Jixie qiangdu)
Based on ANSYS,a finite element model of calculating stress intensity factor（ SIF） for 300 M steel M（ T）sample with different thickness was established and the numerical solutions of SIF for different thickness were compared. The aN curves were accordingly fitted through the SIF numerical solutions and the SIF analytical solutions of different thickness and the Paris formula. And the fitting curves were compared with the experimental data. The results show that the thickness effect influences the finite element numerical solutions of SIF considerably and for the analytical solutions of different thickness,the numerical solutions have certain thickness correction.